Konstruksi Islam Moderat Dan Implementasinya Dalam Pendidikan Islam (Studi Pemikiran Syekh Wahbah Az Zuhaili) - Ramadhan, Bilal; Shohib, Muhammad (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
The research uses a qualitative approach with a library research method. Data collection is done through document review, while data analysis involves content analysis and historical analysis techniques. The content analysis method consists of six stages: comparison, sample selection, recording, exploration, drawing objective conclusions, and narration. A validity test is then conducted to ensure the accuracy and reliability of the data. The research findings show that Sheikh Wahbah Az-Zuhaili’s concept of moderate Islam includes: first, a moderate approach to Islamic law (fiqh); second, tolerance for differences; third, an emphasis on social justice; fourth, simplicity in religion; and fifth, maintaining the integrity of the ummah (community). The Islamic education he advocates is based on key values, including: first, the integration of religious and general knowledge; second, a balance between this world and the hereafter; third, the cultivation of noble character; fourth, tolerance for diversity; and fifth, social justice, creativity, and independence.